Book Reviews (Totalitarian movements and political religions, 2001)
Author: COMBE, SONIA; Une société sous surveillance. Les intellectuels et la Stasi; Reviewer: Brady Brower; Authors: NIEWYK, DONALD and NICOSIA, FRANCIS; The Columbia Guide to the Holocaust; Reviewer: Max Likin